Implementation of the General Administrative Management Information System at Victory University of Sorong - Melda Agnes Manuhutu; Lulu J. Uktolseja; Sarsa F. Sitaniapessy; Cynthya A.K. Maradesa; Meldi Manuhutu; Abraham Manuhutu (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Management Information System is a comprehensive, coordinated and rationally integrated set of information subsystems capable of transforming data into information through a series of ways to increase productivity in accordance with the style and nature of managers on the basis of established data quality criteria. Technological developments require every institution, both government and private, to provide services to be able to serve effectively and efficiently. Management is defined as a typical process consisting of planning, organizing, implementing and monitoring carried out to determine and attempt to achieve goals by utilizing human resources and other resources. In the work process of Victory Sorong University, the General Administration Bureau (ADUM) carries out administrative management processes still manually, this can be seen from the survey results that the data management process is carried out in manual books. This is a major issue that needs attention. Manual conditions can support data loss due to several factors. The importance of the role and function of general administration management as the main task of a government agency, private or organization, so it is necessary to implement an integrated information system using PHP and MySQL database.